Development of data structure of information technology of group spectrum-current diagnosis of induction motors - Кузнєцов, Денис Іванович; Купін, Андрій Іванович (Technology audit and production reserves, 2014)
For monitoring the current status of electrical equipment, the information technology of a group spectrum-current diagnosis of induction motors is proposed. The proposed technology is based on the process of obtaining information about the objects under investigation by analyzing the current spectrum of consuming electrical network. The process of obtaining and further processing of data is considered in the paper. The structure of the database and knowledge base of an expert system as a part of a decision support system for monitoring the current status of induction motors is given. As a result of the conducted studies, the analysis of information processes in the decision support system (DSS) of the information technology of the group spectrum-current diagnosis of induction motors (IM) is made. As a result, the algorithm of the database management system operation (DBMS) for sustainable recording, storing and processing of the necessary data is formed. The structure of the database and knowledge base is developed. The obtained structures of the database and knowledge base can be used in the implementation of systems for monitoring the current status of induction motors based on the spectrum-current diagnosis.